A double helix approach: a proposal to forge a better integration of analysis and process in policy development. (1st January 2003) - Edelenbos, Jurian; Monnikhof, Rene; van Riet, Odette de
In this article, we distinguish two approaches of policy making - the analytical and the process management approach. The first stresses the importance of creating a substantively sound policy, the latter focuses on the process of policy development. In the past, the two camps have been partially ignoring each other, with the result that the one approach misses what the other approach possesses. We try to create an integration of the two visions by developing a double helix approach on policy development. We have designed this double helix approach by identifying the potential risks of the analytical and the process management approach. We use these risks for constructing bridges between the two approaches. In this way, the bridges form the principles of the double helix approach, which are described in detail in this article.